2015 : de tijd loopt : actieboek 2005 - De Mets, Jan; Adriaensen, Rob; Demedts, Bart; Dobbelaere, Griet (Brussel: 11.11.11, 2005)
"Eindredactie: Jan De Mets ; Werkten mee: Rob Adriaensen, Bart Demedts, Griet Dobbelaere, ... et al."